Micropropagation of Zuccagnia punctata, an argentine medicinal plant, by means of “in vitro” technology to promove its conservation and the sustainable production of bioactive compounds - Álvarez, María A. (2024)
Zuccagnia punctata Cav. (“jarilla poposa”) is a monotypic argentine native medicinal plant used by indigenous communities for the treatment of several pathologies. The pharmacological properties have been scientifically validated and its potential use in phytocosmetic and pharmaceutic industry as antiaged, hypoglycemic, anti-inflammatory, antitumoral, antioxidant, antibacterial and antimicotic has been previously demonstrated. However, the species has a low propagation rate in natural conditions and has been included in the preliminary red list of endangered plants in category 3. Therefore, it is necessary to develop methodologies leading to its conservation and propagation to achieve its sustainable use. The objective of this work is to perform a micropropagation protocol for Z. punctata species for the sustainable use and conservation of this species. Furthermore, the study evaluated also the impact of “in vitro” propagation on the content of bioactive compounds of ethanolic extracts obtained from Z. punctataplants obtained “in vitro” with collected wild plants. Seeds have been used as mother material. The seed germination to obtain explants were performed on Murashige and Skoog medium (MS) without plant growth regulators (PGRs) containing sucrose, agar, and ascorbic acid. The same medium was employed for the multiplication of shoots. “In vitro” rooting was achieved in liquid and semisolid medium, and a higher yield was obtained in the latter. The plants were transferred into commercial substrate and acclimatized in a greenhouse. The micropropagated plants (MP) had a high content of total phenolic compounds similar to those obtained from wild adult plants (WAP) collected in the Monte Desert. The flavonoid content of MP was higher than that of WAP. The main chalcones identified in WAP, 2′,4′ dihydroxychalcone (DHC) and 2′,4′-dihydroxy-3′-methoxychalcone (DHMC) were also present in the MP with a rate 1/1, and 1/3 in WAP. The extracts obtained from the MP showed antioxidant, antiinflammatory and antimicrobial activity, similar to WAP. The “in vitro” propagation and acclimatization of Z. punctata constitutes a fundamental tool to achieve large-scale multiplication of this species in the future and the sustainable production of bioactive compounds with commercial applications. Reimplantation in the natural habitat could prevent the loss of this medicinal genetic resource.